A Novel Compact Dual-Polarized Antenna - Yong Cheng; Yadan Li; Wenjun Lu (International Journal of Antennas and Propagation)
A novel compact dual-polarized antenna is proposed. The antenna has a 1.43% impedance bandwidth which is from 1801 MHz to 1827 MHz for return loss larger than 10 dB. The isolation between the two ports is above 28 dB in the bandwidth, and the gain is 6.6 dBi. The proposed antenna not only consists of a full-planar structure, but also is easy to be fabricated for its simple structure. Additionally, a section of slots and slits is cut on the radiation patch to reduce the area of it to 54% compared with the conventional square patch.